2021
DOI: 10.1371/journal.pone.0258032
|View full text |Cite
|
Sign up to set email alerts
|

Viral suppression among middle-aged and aging MSM living with HIV: Partnership type and quality

Abstract: Functional support—the availability of material aid, emotional support, or companionship—promotes general well-being. For men who have sex with men (MSM) living with HIV, having a person who supports you associates with viral suppression. This study examines the association between supportive partnerships and HIV viral suppression among middle-aged and aging MSM living with HIV. A total of 423 middle-aged and aging MSM (mean age, 58.2 years) from the Multicenter AIDS Cohort Study provided self-reported data ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Recent findings from the Multicentre AIDS Cohort Study in the USA showed that being in relationships was associated with viral suppression among middle-aged MSM living with HIV. 34 The increasing likelihood of serodiscordant relationships due to the effectiveness of TasP may act as a motivating factor to further increase rates of viral suppression among HIV-positive MSM, including the small proportion of participants in this study who were not receiving treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Recent findings from the Multicentre AIDS Cohort Study in the USA showed that being in relationships was associated with viral suppression among middle-aged MSM living with HIV. 34 The increasing likelihood of serodiscordant relationships due to the effectiveness of TasP may act as a motivating factor to further increase rates of viral suppression among HIV-positive MSM, including the small proportion of participants in this study who were not receiving treatment.…”
Section: Discussionmentioning
confidence: 95%